Does the use of an orthotic increase comfort, decrease injury and improve running performance? - Robert Baxter; Kirk Chalmers; Amber Hurry; Kantida Koysombat; Fionnuala Geoghegan; Peter Malkin; George Ampat (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2018)
Background: Running is a widely accessible sport with millions of participants in the UK alone. Whilst running has been recognised to have significant health benefits, it does come with a risk of injury. Running-related injuries (RRIs) are seen more commonly in novice runners compared to athletes. Currently, there is ongoing debate as to what is the major cause of RRIs with some suggesting it is down to the differences in striking pattern. RRIs cause a substantial economic burden. There is no clear guidance as to whether the use of an orthotic truly prevents injury and improves running performance. Methods: The study will include 100 voluntary participants and last a total of six weeks with the first two being an adjustment period and the subsequent four weeks being the true study period. Prior to the start of the study, each participant will have their baseline history recorded which will involve them declaring any previous RRIs and the distance they run per week. An Aetrex® IStep® (Aetrex Worldwide, Inc. 414 Alfred Avenue Teaneck, NJ 07666, USA) scan will also be performed to determine their foot type. In the true study period, participants will be required to wear the orthotic on alternating weeks. Participants will run with the orthotic during week 1 and week 3 and without during week 2 and week 4. They are responsible for recording their own data which will consist of the distance run, whether or not the orthotic was worn and also the level of discomfort felt following the run. The level of discomfort will be measured using an 11 point Likert scale. The data will be stored in password secured computers and analysed using the Students T test.